Pengaruh Terapi Touch and Talk Terhadap Kecemasan Anak Usia Pra Sekolah - Novia Ika Pratiwi; Irdawati Irdawati (Jurnal Berita Ilmu Keperawatan, 2019)
Anxiety in children who care in hospitalizatin most be solved. children in preschool age (3-5 years) who received invasive procedure in a hospital is a state of crisis due to a change in health status, environment, family factors, habits or procedures that may cause pain so that the loss of independence of children. State of anxiety that occurs in children will be longer the treatment process than increase the risk of nosocomial infection and traumatic posthospitalization. Preschoolers assume pain is something scary, losing a safe environment. Child in the hospital need the participation of the family in the treatment process and they anxiety. therapy to reduce children's anxiety by parents is therapeutic touch and talk. This study aimed to determine the effect of therapeutic touch and talk to the anxiety of preschool who getting invasive at RSUD Dr. Moewardi. The kind of research was quantitative with quasy experimental nonequivalent control group design. The subject were 30 children ( 15 experiment, 15 control) purposive sampling were selected. Using anxiety cheklist in the adaptation of the theory of stuart and sudden was evaluated. The score were examined by independent sample t-test. A result was found that no different score pre test in experiment and control groub (p-value = 0,449) and have a different score post test in experiment and control groub (p-value = 0,000).